The Importance of Positive Culture In Students' Character Education In The Digitalization Era - Mainita; Yulia Santi; Ihsan Murdani (Bansigom Na Publisher, 2025)
Character education has become an increasingly important topic in the digital era due to changes in the way we learn and interact brought about by technological advances. In this era, moral and ethical values ​taught through character education provide an important foundation for students to be able to build good relationships and interact ethically in social and professional life. Integrity, responsibility, empathy, and respect for others are important values to develop in character education. Character education in the digital era plays an important role in helping students develop the ethical and moral values needed to succeed in life. However, the challenges faced in introducing character education in the digital era are the ever-growing digital content and the influence of social media that can damage moral and ethical values. Therefore, character education must be implemented with the right approach and relevant content so that students can understand these values and apply them in their daily lives. Teaching about character education can be integrated into the curriculum in schools and reinforced through online learning and the use of other technologies. Technology can be an effective tool to help students learn about moral and ethical values Character education is becoming increasingly important in the digital era because technological advances have brought changes to the way we learn and interact. In this era, moral and ethical values taught through character education provide an important foundation for students to be able to build good relationships and interact ethically in social and professional life. To face the challenges in introducing character education in the digital era, it is necessary to carry out proper integration into the curriculum in schools, the use of relevant technology.